Cardiac magnetic resonance rapid longitudinal shortening metrics predict cardiovascular outcomes - Haney, Ailís Ceara; Roy, Roman; André, Florian; Chadalavada, Sucharitha; Aung, Nay; Frey, Norbert; Petersen, Steffen E; Salatzki, Janek; Raisi-Estabragh, Zahra (European heart journal - cardiovascular imaging, 2025)
Cardiac magnetic resonance-derived myocardial strain metrics are emerging as powerful early imaging biomarkers for the detection of cardiac dysfunction. This study utilized the UK Biobank to evaluate: (i) best practice for measurement of ‘rapid longitudinal shortening’, a simplified software-independent measure of longitudinal left ventricular (LV) deformation, (ii) correlation and agreement of rapid longitudinal shortening and feature tracking (FT) strain, and (iii) their respective prognostic value.Two rapid longitudinal shortening [long-axis shortening (LS), atrioventricular junction shortening (AVJS)] and three FT strain measures [global longitudinal strain (GLS); global circumferential strain; global radial strain] were derived. Correlation and agreement were assessed using Pearson’s correlation and Bland-Altman plots. Incident events were prospectively tracked over 4.4 (3.6, 5.9) years. The association of deformation metrics with incident outcomes [heart failure (HF), myocardial infarction, stroke, cardiovascular death] was evaluated using Cox regression, adjusting for demographics, lifestyle, clinical factors, LV ejection fraction, and LV mass. The analysis included 45 844 participants (52% females, median 65 years). LS and AVJS showed moderately strong correlation and agreement with GLS. LS, AVJS, and GLS were independently associated with morbidity and mortality outcomes after adjustment. Rapid longitudinal shortening showed comparable predictive value vs. FT strain for incident cardiovascular outcomes: Hazard ratio for incident HF was 0.78 {confidence interval [CI] (0.69-0.88), 0.79 (CI 0.71-0.89), and 0.78 (CI 0.69-0.89)} for AVJS, LS, and GLS respectively.Rapid longitudinal shortening metrics are significant predictors of cardiovascular outcomes comparable to FT strain. Rapid longitudinal shortening is a simple, potentially software- and vendor-independent alternative to FT strain.